Analysis of the stability of linear systems with continuous Markovian jumps - Mayta Guillermo, Jorge Enrique (2020)
In this paper analyzed the stability of linear systems with continuous Markovian jumps. Firstly, the conditions for the Markov chain to be homogeneous and the state space is finite are imposed. Then the types of stability are presented, for example quadratic average stability, stochastic stability, exponential stability and almost certain stability. Stability in quadratic mean is analyzed by the real part of the eigenvalues of a certain matrix. Finally, an equation of Lyapunov is presented.